Arduino Nano Based SPWM (Sine Pulse Wide Modulation) Single Phase DC to AC Inverter - budi pramono jati; Jenny Putri Hapsari (Program Studi Teknik Elektro Universitas Khairun, 2025)
In off grid photovoltaic systems, the DC voltage from PV or batteries must be converted into a sinusoidal AC voltage that matches the AC voltage at home. The problem is that inverters available on the market are expensive. The problem can be solved by making your own SPWM (Sine Pulse Wide Modulation) inverter. This paper discusses the solution to this problem is with making a single-phase SPWM DC to AC inverter with Arduino nano, MOSFET driver IR2110, with full bridge MOSFET with LC filter and step up transformer. Existing Research Objectives, when compared with previous researchers, the existing research gap is that they use half bridge switching, while our research uses full bridge switching. The method used is a single-phase SPWM inverter with a full-bridge MOSFET in the form of design (hardware and software) and testing of AC output voltage, output power, frequency, calculating efficiency. The SPWM inverter section consists of: SPWM signal generator with Arduino nano, Arduino sketch software, MOSFET driver, full-bridge MOSFET switching inverter, LC filter, step up transformer, feedback transformer, SMPS variable voltage power supply. This single phase SPWM inverter is made using 8 pieces of 171A 150V MOSFET, the test results show that when the dc voltage is changed between 21Vdc to 30Vdc the output ac voltage is around 219 Vac to 228Vac, the frequency of the inverter is also stable at 50 Hz, with an average efficiency of 88.36%.